Observations from the Hydrolysis of the Green Sea Urchin (Strongylocentrotus droebachiensis) - Runar Gjerp Solstad; Philip James (Global Challenges, 2023)
Abstract There is a large amount of coproduct generated by the sea urchin fisheries around the world as well as a growing interest in removing large quantities of undersize and low value sea urchins from barren areas in the northern Atlantic and Pacific coasts as well as other areas around the world. The authors believe there is scope to develop a hydrolysate product from this and this study gives preliminary observations on the characteristics of hydrolysate from the sea urchin Strongylocentrotus droebachiensis. The biochemical composition for S. droebachiensis is moisture 64.1%, protein 3.4%, oil 0.9%, and ash 29.8%. Amino acid composition, molecular weight distribution, lipid‐class, and fatty acid composition are also presented. The authors suggest a sensory‐panel mapping be undertaken on future sea urchin hydrolysates. Possible uses for the hydrolysate are unclear at this stage but the combination of amino acids and the relatively high levels of glycine, aspartic acid, and glutamic acid should be further investigated.